Valley-Hall photonic topological insulators with dual-band kink states - Chen, Qiaolu (2020)
Extensive researches have revealed that valley, a binary degree of freedom (DOF), can be an excellent candidate of information carrier. Recently, valley DOF is introduced into photonic systems, and several valley‐Hall photonic topological insulators (PTIs) are experimentally demonstrated. However, in the previous valley‐Hall PTIs, topological kink states only work at a single frequency band, which limits potential applications in multiband waveguides, filters, communications, and so on. To overcome this challenge, here a valley‐Hall PTI, where the topological kink states exist at two separated frequency bands, is experimentally demonstrated in a microwave substrate‐integrated circuitry. Both the simulated and experimental results demonstrate the dual‐band valley‐Hall topological kink states are robust against the sharp bends of the internal domain wall with negligible intervalley scattering. This work may pave the way for multichannel substrate‐integrated photonic devices with high efficiency and high capacity for information communications and processing.